2015
DOI: 10.1097/aln.0000000000000514
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Epidemiology of Postoperative Transfusion-related Acute Lung Injury

Abstract: Background Transfusion-related acute lung injury (TRALI) is the leading cause of transfusion-related death in the United States; however, it remains poorly characterized in surgical populations. To better inform perioperative transfusion practice, and to help mitigate perioperative TRALI, the authors aimed to better define its epidemiology before and after TRALI mitigation strategies were introduced. Methods This retrospective cohort study examined outcomes of adult patients undergoing noncardiac surgery wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
78
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(81 citation statements)
references
References 34 publications
1
78
1
1
Order By: Relevance
“…Son zamanlarda klinik takiplerin istenilen seviyeye gelmesi ve yoğun bakım süreçlerinin iyi işletilmesi ile transfüzyona bağlı komplikasyonların sıklığı çok azalmakla beraber, yüksek riskli major cerrahilerin (aortik vasküler, transplantasyon cerrahisi, özefagus ve akciğer rezeksiyonları gibi) daha sık yapılır hâle gelmesi ile TRALI, transfüzyonun major komplikasyonlarından biri olarak daha sık görülür hâle gelmiş-tir [6] .…”
Section: Discussionunclassified
“…Son zamanlarda klinik takiplerin istenilen seviyeye gelmesi ve yoğun bakım süreçlerinin iyi işletilmesi ile transfüzyona bağlı komplikasyonların sıklığı çok azalmakla beraber, yüksek riskli major cerrahilerin (aortik vasküler, transplantasyon cerrahisi, özefagus ve akciğer rezeksiyonları gibi) daha sık yapılır hâle gelmesi ile TRALI, transfüzyonun major komplikasyonlarından biri olarak daha sık görülür hâle gelmiş-tir [6] .…”
Section: Discussionunclassified
“…This indirect measurement approach is necessary because of the requirement that the system be nonintrusive to the end user -we cannot simply ask the provider if they've made a decision about a transfusion at the time of an alert. It is also necessary because TACO and TRALI are frequently overlooked in clinical practice and are widely considered to have significantly underreported incidences [3,4,10,11]. This obviates comparing incidence rates based on directly charted diagnoses before and after deployment as an appropriate performance metric.…”
Section: Future Work and Conclusionmentioning
confidence: 99%
“…For the retrospective chart review we will follow a procedure similar to that used in [3][4][5]. Using data from the Perioperative Datamart, a natural language processing (NLP) enhanced version of a surveillance algorithm [13] will identify patients who are likely to have suffered transfusionrelated complications.…”
Section: Future Work and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two adverse reactions in particular, transfusion-related acute lung injury (TRALI) and transfusion-associated circulatory overload (TACO), described in [3], are especially problematic: Between 2009 and 2013, TRALI accounted for 30–45% of reported transfusion-related fatalities, and TACO accounted for 13–34% [2]. Furthermore, recent studies [4, 5] of a non-cardiac surgical patient subpopulation found that those experiencing TACO or TRALI stay in both the ICU and hospital roughly twice as long as those who do not, and have in-hospital mortality rates that are respectively 3.5 and 10 times greater. Consequently, these adverse events not only put the patients at a much higher risk of mortality and poor quality of life outcomes, but also lead to increased utilization of healthcare services potentially leading to an increase in healthcare cost and expenditure.…”
Section: Introductionmentioning
confidence: 99%